Predictive values of cervix length measurement based on transvaginal ultrasonography - Wu, Qian; Zang, Ruiqi; Zhang, Yong (Technology and health care, 2024)
BACKGROUND: Pregnancy is an important process in women’s life, which is widely concerned by women. In recent years, the incidence of premature delivery (PTD) becomes more and more higher due to the development of auxiliary reproduction and ovulation induction technologies and the changes of pregnant women’s lifestyle and physical quality. PTD not only affects postpartum recovery and causes great physical pains, but it also has adverse effects on the birth state of neonates and even leads to neonatal death OBJECTIVE: The predictive values of cervix length (CL) measurement based on transvaginal ultrasonography (TVUS) and pathological examination of placenta for premature delivery (PTD) were investigated and the correlation between PTD and infection was analyzed. METHODS: 120 pregnant women with PTD or high-risk factors for PTD admitted to The Affiliated Hospital of Southwest Medical University between February 2020 and March 2022 were included as the subjects and underwent pathological examination of placenta and TVUS for CL measurement. The final gestational age was set as the standard for the evaluation on the predictive values of pathological examination of placenta and TVUS. What’s more, 36 subjects in PTD group and 84 in normal delivery group (control group) underwent pathological examination of placenta for the analysis of the correlation between PTD and infection. RESULTS: The joint inspection method showed significantly better sensitivity, specificity, PPV, and NPV compared to single CL or pathological examination of the placenta (P< 0.05). Among pregnant women, those with CL ⩽ 30 mm and positive placental pathology had a higher proportion compared to those with CL > 30 mm and negative placental pathology (P< 0.05). Furthermore, the incidence of Ureaplasma Urealyticum (UU), Chlamydia Trachomatis (CT), and Chorioamnionitis (CA) in vaginal discharge of the preterm delivery (PTD) group was significantly higher than that of the control group (P< 0.05). CONCLUSION: The combination of CL ⩽ 30 mm and positive placental pathology could effectively predict PTD and placental infection was notably correlated with the occurrence of PTD.